Study of mechanical joint strength of aluminum alloy 7075-T6 and dual phase steel 980 welded by friction bit joining and weld-bonding under corrosion medium. (15th March 2015) - Lim, Yong Chae; Squires, Lile; Pan, Tsung-Yu; Miles, Michael; Song, Guang-Ling; Wang, Yanli; Feng, Zhili
Highlights: Friction bit joining (FBJ) and weld-bonding (adhesive + FBJ) processes. FBJ to spot weld high-strength Al alloy to high-strength steel. Lap shear strength of ∼10 kN for high-strength Al alloy to high-strength steel. Effective corrosion mitigation by combining FBJ with adhesive. Abstract: In this work, we have employed a unique solid-sate joining process, called friction bit joining (FBJ), to spot weld aluminum alloy (AA) 7075-T6 and dual phase (DP) 980 steel. Static joint strength was studied in the lap shear tension configuration. In addition, weld-bonding (adhesive + FBJ) joints were studied in order to evaluate the ability of adhesive to mitigate the impact of corrosion on joint properties. Accelerated laboratory cyclic corrosion tests were carried out for both FBJ only and weld-bonding joints. The FBJ only joints that emerged from corrosion testing had lap shear failure loads that were significantly lower than freshly prepared joints. However, weld-bonding specimens retained more than 80% of the lap shear failure load of the freshly prepared weld-bonding specimens. Examination of joint cross sections confirmed that the presence of adhesive in the weld-bonding joints mitigated the effect of the corrosion environment, compared to FBJ only joints.